Quality of three techniques for root canal filling: an in vitro cross-sectional analysis in mandibular molars - Rodrigues, Carla Roberta Souza; Patara, Tatiany Sanches Leite; Batista, Victor Eduardo de Souza; Verri, Fellippo Ramos [UNESP]; Mori, Graziela Garrido (Dental Press International, 2019)
Introduction: Reciprocating system can prepare the root canal using only one instrument. However, to ensure successful endodontic treatment, it must result in high-quality root canal filling. In this regard, several techniques can be used, and it is important that their efficiency is determined. This study analyzed three different techniques in terms of their ability to fill root canal. Material and Methods: The study involved 30 extracted human mandibular molars. Mesial canals of these teeth were instrumented using WaveOne system and then divided into three groups according to the technique used for root canal filling. The single-cone technique, Tagger’s hybrid technique, and an experimental technique (single-cone plus gutta-percha condenser) were used for Groups I, II, and II, respectively. Filled teeth were sectioned transversely into 0.3-mm sections 2, 4, and 6 mm from the root canal apex. The sections were then digitized and analyzed. Data were statistically compared using Kruskal-Wallis and Dunn tests, with p-values < 0.05 indicating significance. Results: There was no significant difference among experimental groups in terms of the amount of gutta-percha or sealer used. However, in Groups II and III, there were fewer voids in root canal filling than in Group I (p < 0.05). Conclusion: The techniques for root canal filling presented in the current study yielded a low number of empty spaces, and thermoplastification techniques result infewer voids.
Keywords: Root canal filling; Root canal filling material; Root canal preparation